Penggunaan Aplikasi Simkapel dalam Pengurusan Sertifikat Safe Manning Tb. Samudera Tirta Oleh PT. Berlia Ocean Shipping Dumai - Sri Wahni; Dirhamsyah Dirhamsyah; Irma Handayani; Fadiyah Hani Sabila (Universitas Kristen Indonesia Toraja, 2024)
This paper explains about the Use of Simkapel Application in the Management of Safe Manning Certificate of Tb. Samudera Tirta by Pt. Berlian Ocean Shipping Dumai. PT. Berlian Ocean Shipping Dumai is a company that provides service for both ships and ship crews, from the ship itself to the ship's departure. Procedure for Issuing Shipping Certificate (Safe Manning) at the Office of Shipping Authority Class In Dumai PT.Berlian Ocean Shipping Dumai begins with preparing documents (Application Letter) and its relationship with related agencies, both with government companies carried out by the National Shipping Company. PT.Berlian Ocean Shipping Dumai is one form to maintain the smoothness of the shipping certificate issuance procedure. PT.Berlian Ocean Shipping Dumai takes care of various important documents needed by the ship to carry out each of its operations and also communicates directly with government officials who are in charge of the ship. In addition, PT.Berlian Ocean Shipping Dumai also serves requests to meet the needs of the ship and the ship's airspace. In writing this paper, the author uses the field research method and the library research method which are related to the main data taken.